Preparation, optimization and in vitro–in vivo evaluation of Shunxin sustained release granules - Dou, Yinghuan (Chin Med, 2019)
BACKGROUND: Shunxinzufang decoction is tutors, empirical formula and has been used in Chinese patients of HFpEF for several years. The aim of this study was to make into sustained release granules and select the best formula for the preparation of Shunxin sustained release granules and to evaluate its in vivo and in vitro drug release behavior. METHODS: Response surface methodology and Center composite design were applied to screen the optimal formula of Shunxin sustained release granules. HPLC was used to detect indicative ingredients—paeoniflorin, calycosin-7-glucoside and ferulic acid in Shunxin sustained release granules. The in vitro sustained release character of indicative ingredients was investigated in simulated digestive fluids. In-vivo process of active components was studied through pharmacokinetics. RESULTS: The optimal formula of Shunxin sustained release granules consisted of 35% shunxinzufang extract and 65% HPMC/starch (HPMC/starch ratio = 2:1). Three indicative components can be separated well under selected HPLC conditions. Compared with Shunxinzufang extract, the active components of Shunxin sustained release granules have obvious sustained-release character and improved bioavailability. CONCLUSION: Shunxin sustained release granules has obvious sustained-release character and improved bioavailability. [Image: see text]